If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2y = 36 Solving 3x + -2y = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 3x + -2y + 2y = 36 + 2y Combine like terms: -2y + 2y = 0 3x + 0 = 36 + 2y 3x = 36 + 2y Divide each side by '3'. x = 12 + 0.6666666667y Simplifying x = 12 + 0.6666666667y
| x(x+1)=4.8 | | 2x+7=6x-2*(3x-1) | | 10z+7=5z+9 | | 16x^2+20x=0 | | (12x-11)(8x-5)=0 | | 3x^2+7x-11=-5x+4 | | x+38=-42 | | 118-4x=4x+14 | | -16x+92=-42 | | 1-y=6 | | 0.2x+1=0 | | -4b-28=0 | | t-(-10)=-8 | | 7x-2y=31 | | 7-63x=12 | | -5-b=2a | | 3x^2-14x=-3 | | -5-b= | | (u)3-7u-6ifu=-2 | | -5-6=2a | | 12x+90=85 | | a+3b=-2 | | 7(y-6)=28 | | 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 |